Hubungan Antara Personal Hygiene dengan Kejadian Skabies pada Anak Remaja di Pondok Pesantren Putri Al-Izzah Bandungrejo Mranggen Demak - Nazil Wilda Quthrunnada; Kurnia Wijayanti; Nopi Nur Khasanah (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2025)
Background: Dermatological conditions remain a concern worldwide, especially in Indonesia. In 2016, data from the Ministry of Health of the Republic of Indonesia revealed that, out of a population of 216.6 million, the prevalence of scabies varied between 4.60% and 12.95%. Adolescence is a phase in which individuals develop and show their first secondary sexual characteristics until they reach sexual maturity. Personal hygiene is an effort to live a healthy lifestyle, which includes public health and hygiene in various activities. The purpose of this study was to determine the relationship between personal hygiene and the incidence of scabies among adolescents at Pon.dok Pesa.ntren Putri Al-Iz.zah Band.ungrejo Mrang.gen D.emak... Method This study used a cross-sectional design with 242 female students as subjects. Data were collected using a questionnaire. Spearman rank test was used to evaluate the relationship between personal hygiene and the incidence of scabies among adolescents at the Al-Izzah Islamic Boarding School, Bandungrejo, Mranggen, Demak... Results: Spearman rank test study revealed a relationship between personal hygiene and the prevalence of scabies among adolescents at the Al-Izzah Islamic Boarding School, Bandungrejo, Mranggen, Demak, with a p value of 0.000. This indicates a statistically significant correlation between personal hygiene and the incidence of scabies. The calculated R value of 0.54 indicates a moderate correlation between these variables at the institution. Conclusion There is a relationship between personal hygiene and the incidence of scabies in adolescents at the Al-Izzah Islamic Boarding School, Bandungrejo, Mranggen, Demak.